Penerapan Metodologi Ilmiah dalam Proses Pembelajaran di Raudlatul Athfal: Kajian Observasional pada RA Al-Wafi - Izzah, Ikfina Nurul; Nugraha, Mulyawan Safwandy (Peneliti.net, 2025)
This study aims to examine the application of scientific methodology in the learning process at Raudlatul Athfal (RA). Through a descriptive qualitative approach, data were obtained from observations, interviews, and documentation. The results showed that the use of scientific methods, such as simple experiments and observations, help children develop critical thinking skills and curiosity. However, some of the obstacles faced are limited facilities and lack of training for teachers. This study highlights the importance of teacher training in the implementation of scientific methodology in order to create effective learning and support children's holistic development.